BMP‐2 induces human mononuclear cell chemotaxis and adhesion and modulates monocyte‐to‐macrophage differentiation. Issue 11 (13th August 2018) - Pardali, Evangelia; Makowski, Lena‐Maria; Leffers, Merle; Borgscheiper, Andreas; Waltenberger, Johannes
Abstract: Type 2 diabetes mellitus (T2DM) is a cardiovascular risk factor which leads to atherosclerosis, an inflammatory disease characterized by the infiltration of mononuclear cells in the vessel. Bone morphogenetic protein (BMP)‐2 is a cytokine which has been recently shown to be elevated in atherosclerosis and T2DM and to contribute to vascular inflammation. However, the role of BMP‐2 in the regulation of mononuclear cell function remains to be established. Herein, we demonstrate that BMP‐2 induced human monocyte chemotaxis via phosphoinositide 3 kinase and mitogen‐activated protein kinases. Inhibition of endogenous BMP‐2 signalling, by Noggin or a BMP receptor inhibitor, interfered with monocyte migration. Although BMP‐2 expression was increased in monocytes from T2DM patients, it could still stimulate their migration. Furthermore, BMP‐2 interfered with their differentiation into M2 macrophages. Finally, BMP‐2 both induced the adhesion of monocytes to fibronectin and endothelial cells (ECs), and promoted the adhesive properties of ECs, by increasing expression of adhesion and pro‐inflammatory molecules. Our data demonstrate that BMP‐2 could exert its pro‐inflammatory effects by inducing monocyte migration and adhesiveness to ECs and by interfering with the monocyte differentiation into M2 macrophages. Our findings provide novel insights into the mechanisms by which BMP‐2 may contribute to the development of atherosclerosis.